School Management and Leadership in Aulas Ocupacionales of the Region of Murcia - Cutanda-López, María Trinidad; Alfageme-González, María Begoña (Avances en Supervisión Educativa, 2025)
This contribution, derived from a doctoral thesis (Cutanda-López, 2019), addresses the roles of management and leadership in a school re-engagement programme. Taking an ecological approach to school risk as a starting point, it highlights the importance of leadership inclusive and for social justice as a way of transformation and improvement. It is based on a Mixed Method Approach - Multilevel Nested Convergent Multilevel Design of Qualitative Dominant Method (DIACNIV) - with information derived from semi-structured interviews with the administration staff involved in the programmes analysed. The results place administration at the crossroads of different levels, which makes management vs. leadership functions prevail: macro (emergency reforms - homogenised - insufficient), meso (structural and cultural barriers), and micro (deficiencies in teacher and management training). It is worth concluding that it is necessary and difficult to move towards a project based on moral commitment and collective responsibility, driven by inclusive leadership.
Keywords: Inclusive education; social inclusion; social justice; leadership; educational programs